ANALISIS PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT TIOKINDO ELECTRIC - Rahakbauw, Oktovina Deci; Berliana, Rizma (Management Research and Business Journal, 2025)
This research aims to determine the influence of Leadership Style, Motivation and WorkDiscipline on Employee Performance at PT Tiokindo Electric. The data used in this research ispremier data obtained from distributing questionnaires. The total population was 41 respondentsusing a saturated sample, so data collection was carried out by distributing questionnaires to 41employees. The data analysis method used is multiple linear regression analysis, with coefficientof determination analysis, t test and F test, multiple linear regression analysis produces theequation Y = 1.815 + 0.283X1 + 0.615X2 + 0.438X3. The employee coefficient test results are 0.709or 70.9% of performance is influenced by the variables of leadership style, motivation and workdiscipline. Meanwhile, the remaining 29.1% was influenced by other factors not explained in thisstudy. The results of the t test show that Leadership Style (X1) has a tcount of 2.315 and a ttableof 1.687, the value of tcount > ttable where 2.315 > 1.687, apart from that, the significant value is0.026, the value is 0.026 < 0.05, so Ha1 is accepted and Ho1 is rejected. Motivation (X2) has atcount of 2.727 and a t table of 1.687, the value of tcount > ttable where 2.727 > 1.687, apart fromthat, the significant value is 0.010, the value is 0.010 < 0.05, so Ha2 is accepted and Ho2 is rejected.Work Discipline (X3) has a tcount of 1.917 and a ttable of 1.687, a value of tcount > ttable where1.917 > 1.687, apart from that, the significant value is 0.063, a value of 0.063 < 0.05, so Ha3 isrejected and Ho3 is accepted. So the variables Leadership Style, Motivation have a positive andsignificant effect partially and Work Discipline has no significant effect partially. The significantvalue of the F test results is 0.000, which is smaller than 0.05. It can be concluded that there is asimultaneous influence between Leadership Style, Motivation and Work Discipline on EmployeePerformance.